Leveraging law and ethics to promote safe and reliable AI/ML in healthcare - Drabiak, Katherine (Frontiers in Nuclear Medicine, 2022)
Artificial intelligence and machine learning (AI/ML) is poised to disrupt the structure and delivery of healthcare, promising to optimize care clinical care delivery and information management. AI/ML offers potential benefits in healthcare, such as creating novel clinical decision support tools, pattern recognition software, and predictive modeling systems. This raises questions about how AI/ML will impact the physician-patient relationship and the practice of medicine. Effective utilization and reliance on AI/ML also requires that these technologies are safe and reliable. Potential errors could not only pose serious risks to patient safety, but also expose physicians, hospitals, and AI/ML manufacturers to liability. This review describes how the law provides a mechanism to promote safety and reliability of AI/ML systems. On the front end, the Food and Drug Administration (FDA) intends to regulate many AI/ML as medical devices, which corresponds to a set of regulatory requirements prior to product marketing and use. Post-development, a variety of mechanisms in the law provide guardrails for careful deployment into clinical practice that can also incentivize product improvement. This review provides an overview of potential areas of liability arising from AI/ML including malpractice, informed consent, corporate liability, and products liability. Finally, this review summarizes strategies to minimize risk and promote safe and reliable AI/ML.